Beyond windrush : rethinking postwar anglophone caribbean literature - Brown, J. Dillon, 1971-; Rosenberg, Leah (Caribbean studies series (Jackson, Miss.), 2015)
"This edited collection challenges a long sacrosanct paradigm. Since the establishment of Caribbean literary studies, scholars have exalted an elite cohort of émigré novelists based in postwar London, a group often referred to as "the Windrush writers" in tribute to the SS Empire Windrush, whose 1948 voyage from Jamaica inaugurated large-scale Caribbean migration to London. In critical accounts this group is typically reduced to the canonical troika of V.S. Naipaul, George Lamming, and Sam Selvon, effectively treating these three authors as the tradition's founding fathers. These "founders" have been properly celebrated for producing a complex, anticolonial, nationalist literature. However, their canonization has obscured the great diversity of postwar Caribbean writers, producing an enduring but narrow definition of West Indian literature. Beyond Windrush stands out as the first book to reexamine and redefine the writing of this crucial era. Its fourteen original essays make clear that in the 1950s there was already a wide spectrum of West Indian men and women--Afro-Caribbean, Indo-Caribbean, and white-creole--who were writing, publishing, and even painting. Many lived in the Caribbean and North America, rather than London. Moreover, these writers addressed subjects overlooked in the more conventionally conceived canon, including topics such as queer sexuality and the environment. This collection offers new readings of canonical authors (Lamming, Roger Mais, and Andrew Salkey); hitherto marginalized authors (Ismith Khan, Elma Napier, and John Hearne); and commonly ignored genres (memoir, short stories, and journalism)."--